2021
DOI: 10.1016/j.ijid.2021.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an inactivated Covid19 vaccine-induced antibody response with concurrent natural Covid19 infection

Abstract: Objectives The risk of contracting SARS-CoV-2 is high among the health care workers (HCW). The comparison between the antibody response to an inactivated Covid19 vaccine and the antibodies that developed during Covid-19 infection has not been elucidated. In this study, vaccine-induced antibody levels were compared with the antibodies developed in naturally infected HCWs. Methods Eighty vaccinated individuals and 80 Covid-19 patients enrolled to the study. Both groups were matched on age, gender and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Similarly, there was poor induction of anti-N antibodies after vaccination of naïve individuals with CoronaVac, overall confirming that this vaccine is a poor inducer of antibody responses against this protein. 32 , 33 , 34 This is important to note, given that the protection afforded by CoronaVac is most likely due to the induction of nAbs responses, and additional immune mechanisms such as Fc-effector functions and T-cell immunity, which contribute to improve disease outcome. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was poor induction of anti-N antibodies after vaccination of naïve individuals with CoronaVac, overall confirming that this vaccine is a poor inducer of antibody responses against this protein. 32 , 33 , 34 This is important to note, given that the protection afforded by CoronaVac is most likely due to the induction of nAbs responses, and additional immune mechanisms such as Fc-effector functions and T-cell immunity, which contribute to improve disease outcome. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Anti-N antibodies have been reported as indicators of natural infection [ 2 , 8 ]. Azak et al reported that the positive rates of anti-N in vaccinated and infected patients were 51.2% and 98.8%, respectively [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…For serological measurement of SARS-CoV-2 antibodies, tests that detect antibodies to S and N proteins, which are the most immunogenic proteins of SARS-CoV-2, are mainly used. Various studies reported the characteristics and quantitative values of the anti-S and anti-N antibodies against SARS-CoV-2 depending on whether the subjects were infected or vaccinated [ 7 , 8 , 9 ]. The spike (S) protein, which is present on the envelope of SARS-CoV-2, allows the virus to connect with human cells and has been reported to exert neutralizing effects in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Two inactivated vaccines have been reported to effectively induce antibody responses and prevent COVID-19, including severe diseases and death (14)(15)(16). Some studies reported that antibody titer could decrease gradually over a year; meanwhile, antibodies against spike protein of SARS-CoV-2 are crucial for neutralizing the virus (16,17). Humoral response quantification is becoming important to assess the vaccine response.…”
Section: Resultsmentioning
confidence: 99%